Albert Voorhies, Ex-Justice, Revised Laws of Louisiana, Approved March 14th, 1870, with Copious References to the Acts of the Legislature from and Including the Sessions of 1870, up to and Including the Session of 1882. Second Edition Page 161, Image 171, § 949 (1884) - (:unkn) unknown (General Publisher, 1884)
When gunpowder is shipped on board of a steamboat it shall be stored away at as great a distance as possible from the furnace, and a written notification of the fact shall be placed in three conspicuous parts of the boat; and in the event of such notification not being so exhibited, then for any loss of property or life for which the powder may be deemed the cause, the owner and captain shall be liable to the penalty provided in the proceeding section. § 950. Any person who shall ship or put on board, or cause to be shipped or put on board of any steamboat within this State, any gunpowder, without giving notice thereof, at the time of making the shipment, to the master or clerk of said boat, shall be liable to a penalty of two hundred dollars
--
Keywords: GUN POWDER TRANSPORTATION